Pengaruh Motivasi Dan Kompetensi Terhadap Kinerja Pegawai Pada Puskesmas Ge’tengan Kecamatan Mengkendek - Krislegino Krislegino; Adriana Madya Marapa; Rahma. G. Tammu (Transformasi: Journal of Economics and Business Management, 2023)
The purpose of this study was to analyze the influence of motivation and competence on employee performance at the ge’tengan health center. The type of research. With a population of all employees of the ge’tengan and the sample used in this study totaling 50 people. The data analysis techniques used were validity test, reliability test, multiple liner regression test, partial test (t), simultaneous test(f), correlation test, and determination test. Date was processed using 25. Bassed on the result pf partial tests (1) the calculated F value was 15,182>3,19 so that it could be concluded that motivasion and competence simultaneously affect employee performance. While significantly 0,000<0,05, it means that H3 is accepted or in other words motivation and competence simultaneously affect employee performance